The Evaluation of The Achievement Sport Development Program Regional Student Sports Education and Training Centers (PPLOPD) in Kendal Regency (Journal of Physical Education and Sports, 2022)
Sport training and development are parts of efforts to improve the quality of Indonesian people. Systematic sports training, directed at increasing self-control, responsibility, discipline, sportsmanship which in the end can obtain sports achievements that can arouse national pride, one of which is by forming an appropriate forum through the establishment of the Regional Student Sports Education and Training Center (PPLOPD) in each city or regency. The evaluation model is needed together with the implemented program, the researcher chooses the Context, Input, Process, Product (CIPP) model as the evaluation. So that it can determine the overall success of the achievement of coaching program for PPLOPD athletes in Kendal Regency.This research is a qualitative research with a qualitative approach in evaluation program evaluation using the Context-Input-Process-Product (CIPP) model. The research subjects were the PPLOPD Achievement Sports Branch PPLOPD in Kendal Regency, namely athletics, sepak takraw, pencak silat, karate, taekwondo, sand volleyball, bridge, fencing, weightlifting/ heavytlifting, judo, and wrestling including the administrators, coaches, athletes, parents/community , as well as sports facilities and infrastructure in each of the PPLOPD achievement sports. The data collection was carried out by observation, interviews, documentation, and the combinations. The data collection tools are in the form of observations and interviews, while documentation in the form of archives is used as the supporting data. The data validity was carried out using triangulation and observational bending techniques. The qualitative analysis goes through four stages, namely data collection, data reduction, data presentation, and drawing conclusions or verification.The student sports achievement development program in Kendal Regency is seen from the context of the program, namely the existence of the Regional Student Sports Training Center (PPLOPD) program which is categorized as good. The program input is categorized as good in terms of the input of athletes, coaches, and the administrators that selected by the applicable regulations reported to the Kendal Regency Youth, Sports and Tourism Office. The coordinations process between administrators, coaches, athletes, parents, community and agencies is going well. The evaluation and control have been carried out both during and after training. The product program is good, shown by the improvements at the regional and national levels.